2012 IEEE International Ultrasonics Symposium 2012
DOI: 10.1109/ultsym.2012.0284
|View full text |Cite
|
Sign up to set email alerts
|

Non-perturbing cavitation detection / monitoring in sonochemical reactors

Abstract: To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…An alternative method for the measurement of the cavitation frequency spectra is monitoring the electrical signals of the ultrasonic transducers used for excitation. In [12] a feasibility study for this technique has already been conducted. Here the signals of an external microphone, a hydrophone and the transducer's current signal are compared.…”
Section: Cavitation Detection Using Frequency Spectramentioning
confidence: 99%
“…An alternative method for the measurement of the cavitation frequency spectra is monitoring the electrical signals of the ultrasonic transducers used for excitation. In [12] a feasibility study for this technique has already been conducted. Here the signals of an external microphone, a hydrophone and the transducer's current signal are compared.…”
Section: Cavitation Detection Using Frequency Spectramentioning
confidence: 99%
“…Neppiras applied the motional impedance of a focussed ultrasound transducer to analyze the movement of bubbles in 1976 [5]. More recently, a correlation between the onset of cavitation and indicators derived from the driving current signal of a piezoelectric transducer showed the feasibility of this method [1]. The advantage of this method is that it may be easily applied to various ultrasound systems as no changes on the system are required.…”
Section: Cavitation Detection Based On Acoustic Emissionsmentioning
confidence: 99%
“…Thus, alternative methods are desired to quantify cavitation in situ without the necessity of applying sensors in the liquid. In a first feasibility study the feedback of cavitation on the driving signals of a piezoelectric transducer turned out to be a promising method [1]. This paper deals with a more detailed investigation of this method in a broader frequency range, and compares it broadband acoustic emission.…”
Section: Introductionmentioning
confidence: 99%
“…In acoustic cavitation, the generated frequency components are mostly related to the driving frequency f 0 of the ultrasound transducer [3][4][5][6][7][8][9][10]. Researchers [11][12][13][14] have shown that with a so called self-sensing technique, that is using the ultrasound transducer simultaneously as both an actuator and a sensor, indicators for the presence of cavitation can be detected by observing the transducer's electrical signals. By now the transducer data [12,13] have been compared to those of microphones and hydrophones in order to reach a conclusion on the processes in the fluid.…”
Section: Introductionmentioning
confidence: 99%